Forensic insights : unmasking technology-assisted child sexual abuse through the lens of child healthcare workers = Visiones forenses : descubriendo el abuso sexual infantil asistido por tecnología a través de la óptica de los trabajadores de la salud infantil - Marimuthu, Varshini
COVID-19 infection prevention measures have enhanced risks of abuse for children, especially in terms of high vulnerability to technology. Despite the rise in technology-assisted child sexual abuse (TA-CSA), little research has been conducted on Child Healthcare Workers' perceptions beyond reporting on young people's experiences. This novel study aims to understand how Childcare Workers perceive technology-assisted child sexual abuse, risks, impacts, therapeutics, and perceptions of need. Qualitative research methodology was used for the study. Child healthcare workers volunteering to participate in the study were approached by a purposive sampling strategy and interviewed in person. Field notes were taken to record the conversation. Grounded theory approach was used to analyze the results to eliminate bias associated with presumptive knowledge from literature. Participants reported an exponential rise in cases of TA-CSA during the COVID-19 pandemic. Impacts of TA-CSA such as self-blame, fear of offender, and inability to manage emotions were the most common and peculiar aspects of TA-CSA in this population. Though the childcare workers recognized the risks and impacts of TA-CSA, they were unaware of the need for distinct frameworks and therapeutic approaches essential for handling cases of TA-CSA. Complexities in TA-CSA necessitate an algorithm in addressing TA-CSA as a separate entity. Therapy should be focused on the specific impacts of TA-CSA. Further, the observations of the study stipulate the exigent shift in community perspective from blaming the victim to shaming the offender.